What Can Stutterers Learn from the Neurodiversity Movement? - Constantino, Christopher D. (Seminars in Speech and Language, 2018)
Neurodiversity is both an empowerment movement and a way of thinking about disability. Rather than focusing on pathology and impairment, neurodiversity emphasizes natural variation and the unique skills, experiences, and traits of neurodivergent individuals. People who stutter are beginning to work with and derive value from these concepts. In this article, we look at the history of neurodiversity and its key ideas. We discuss the conventional view of disability, the medical model, which situates disability within the individual as pathology. We also take up social and relation models of disability, which situate disability in social oppression or mismatches between individuals and their environment. Neurodiversity has not been without controversy. We look at some of the disagreements surrounding issues of intervention and cure. The ideas of neurodiversity are applied to stuttering, and a case example illustrating therapy using these ideas is given. We conclude that therapy should focus on subject's well-being and not normalization of superficial behaviors.
Keywords: Stuttering; neurodiversity; social model of disability; identity-first; stutterer